Effectiveness of Online Blended Learning and Critical Thinking Skills of Biology Students in Indonesia: Meta-Analysis Study - Arwaty; Rahmah, Andi; Mustamin, Kaso (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to determine the effectiveness of online blended learning and critical thinking skills of biology students in Indonesia.Â This type of research is a meta-analysis study. This research data comes from 13 national and international journals.Â The inclusion criteria of the meta-analysis are publications derived from google Scholar, ScienceDirect, ERIC, Springer, and Pubmed databases, the study has two classes of experiments blended learning and conventional controls, research publications must be indexed by Scopus, SINTA and WOS, research comes from reputable journals or proceedings and sample size (N) > 20 students. Keyword data search consists of blended learning; blended learning on the critical thinking skills of biology students; students’ critical thinking skills; Online blended learning. Data analysis calculates summary effect size, heterogeneity test and analyzes publication bias with JSAP application. The results of the study concluded that the summary effect size value (ES = 1.05) criteria was high and the total sample (N = 1070) of students This finding shows that online blended learning effectively encourages critical thinking skills in biology students compared to conventional learning.